1989
DOI: 10.1007/bf01874773
|View full text |Cite
|
Sign up to set email alerts
|

Species differences in the adrenergic responses of fish red cells: studies on whitefish, pikeperch, trout and carp

Abstract: The occurrence and pH dependence (pHe 7-8) of the adrenergic red cell responses of two salmonids, trout and whitefish, and a percinid, pikeperch were studied. These are all species that live in well-oxygenated waters. The responses were compared to those of carp, which tolerates oxygen-deficient waters.The adrenergic responses of trout and whitefish red cells were pronounced. In these species red cell swelling, the accumulation of sodium and chloride in the cell, and the increase in red cell oxygen content at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…In rainbow trout the response occurs at pH values near 8 and at atmospheric oxygen tension, but is enhanced by a decrease both in pH (Nikinmaa 1983) and Po2 (Motais et al 1987). In carp RBCs the response is only observed at either pH values below 7.5 or at low Po, (Salama and Nikinmaa 1988) and even then the response is much smaller than that in rainbow trout RBCs (Salama and Nikinmaa 1989).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In rainbow trout the response occurs at pH values near 8 and at atmospheric oxygen tension, but is enhanced by a decrease both in pH (Nikinmaa 1983) and Po2 (Motais et al 1987). In carp RBCs the response is only observed at either pH values below 7.5 or at low Po, (Salama and Nikinmaa 1988) and even then the response is much smaller than that in rainbow trout RBCs (Salama and Nikinmaa 1989).…”
Section: Introductionmentioning
confidence: 92%
“…Therefore, I have investigated the effect of oxygen tension on the dose-response relationship between -agonist concentration and cAMP accumulation on the one hand and between -agonist concentration and adrenergic swelling on the other, using three different -agonists (the natural catecholamines adrenaline and noradrenaline, and the pharmacological analogue isoproterenol). The increase in cellular water content gives a reliable estimate of the activation of the adrenergic net ion fluxes (see Salama and Nikinmaa 1989). In addition, I have in the same experiments quantified the amount of cAMP required for the P-adrenergic response in rainbow trout RBCs.…”
Section: Introductionmentioning
confidence: 98%
“…Apparently, carp erythrocytes are stimulated to a significant extent in vivo during deep hypoxia. Although the Na+/H + anti-porter of CRC is less sensitive to the fl-stimulation under normoxic conditions (Salama and Nikinmaa 1989;Holk and Lykkeboe 1995), it has been shown recently that upon adrenergic stimulation the oxygen affinity of CRC is increased to a greater extent than trout erythrocytes despite a smaller change of pHi (Holk and Lykkeboe 1995). It is proposed that a decrease of the hemoglobin concentration of the CRC due to dilution has an important additional impact on the oxygen affinity of carp blood upon adrenergic stimulation (Holk and Lykkeboe 1995).…”
Section: Response Of Erythrocytesmentioning
confidence: 98%
“…Adrenergic responses of erythrocytes were absent in the elasmobranchs Squalus suckleyi and Raja binoculata during normoxia (Tufts and Randall 1989), in the flatfish Platichthys steUatus and in tench Tinca tinca after exhaustive exercise (Milligan and Wood 1987;Jensen 1987), and in the American eel Fluouitla rostrata after aerial exposure (Hyde et al 1987). In a comparative in vitro study, Salama and Nikinmaa (1989) showed that the rate of Na+/H + exchange in carp erythrocytes after adrenergic stimulation in normoxia was at least t0 times lower than in salmonid red cells. The adrenergic induced decrease of the proton gradient across the red cell membrane in vitro was shown to be maximally 0.05 pH units in carp, whereas a change of 0.2 units has been observed in trout (Salama and Nikinmaa 1988).…”
Section: Introductionmentioning
confidence: 97%
“…Environmental hypoxia can induce many compensatory processes in fishes (Salama and Nikinmaa 1989;Fritsche and Nilsson 1993;Hochachka and Lutz 2001), which have been well described for highly sensitive (e.g., rainbow trout; Boutilier et al 1988) and highly tolerant (e.g., African lungfish; Dunn et al 1983) species. These compensatory mechanisms, such as increased ventilatory rate or lowered standard metabolic rate, help fish to survive both shortand long-term hypoxic episodes (Jensen et al 1993).…”
Section: Introductionmentioning
confidence: 99%